1984
DOI: 10.1111/j.2044-8279.1984.tb00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Inferential and Memory Skills in Children's Comprehension of Stories

Abstract: SUMMARY. An experiment was carried out to investigate 7-8 year-olds' use of implicit inferences in understanding stories. Two groups of children, differentiated by their ability at text comprehension, read four short stories and were asked a series of questions after each one. The results showed that skilled readers were better than less skilled readers at answering questions from memory shortly after reading a story, both when the questions could be answered directly from the text, and when they required an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
150
0
20

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(184 citation statements)
references
References 12 publications
12
150
0
20
Order By: Relevance
“…La construcción de un modelo mental requiere que el lector realice inferencias para la construcción de la representación del texto (Van Dijk & Kintsch, 1983;Graesser, et al, 1994;Perfetti, et al, 2005) por lo que resulta esperable que los niños con bajos rendimientos en comprensión posean dificultades en la realización de las mismas y, consecuentemente, fallaran a la hora de la construcción del modelo mental. Los datos arrojados por este estudio se encuentran en consonancia con los resultados de otras investigaciones que han establecido la existencia de diferencias en función del proceso inferencial en grupos de buenos y malos comprendedores (Bowyer-Crane & Snowling, 2005;Cain et al, 2004;Cain & Oakhill, 1999;Oakhill, 1984;Yuill & Oakhill, 1991). Se ha constatado que los comprendedores con rendimientos bajos tienen problemas para hacer inferencias, según Yuill y Oakhill (1991) esto ocurre porque no se pueden despegar de los aspectos concretos del texto poseyendo un comportamiento pasivo frente a la lectura.…”
Section: Discussionunclassified
“…La construcción de un modelo mental requiere que el lector realice inferencias para la construcción de la representación del texto (Van Dijk & Kintsch, 1983;Graesser, et al, 1994;Perfetti, et al, 2005) por lo que resulta esperable que los niños con bajos rendimientos en comprensión posean dificultades en la realización de las mismas y, consecuentemente, fallaran a la hora de la construcción del modelo mental. Los datos arrojados por este estudio se encuentran en consonancia con los resultados de otras investigaciones que han establecido la existencia de diferencias en función del proceso inferencial en grupos de buenos y malos comprendedores (Bowyer-Crane & Snowling, 2005;Cain et al, 2004;Cain & Oakhill, 1999;Oakhill, 1984;Yuill & Oakhill, 1991). Se ha constatado que los comprendedores con rendimientos bajos tienen problemas para hacer inferencias, según Yuill y Oakhill (1991) esto ocurre porque no se pueden despegar de los aspectos concretos del texto poseyendo un comportamiento pasivo frente a la lectura.…”
Section: Discussionunclassified
“…In line with the research presented above, several studies have indicated that children are able to integrate information within a single text (Cain & Oakhill, 1999;Oakhill, 1982Oakhill, , 1984, and that they make connections between text information and background knowledge (Barnes, Dennis, & Haefele-Kalvaitis, 1996;Cain, Oakhill, Barnes, & Bryant, 2001). It is important to note, however, that participants in these studies were explicitly prompted to combine and integrate information, for example by integration-promoting questions.…”
Section: Integration Within Single Textsmentioning
confidence: 77%
“…Este tipo de pergunta, por demandar como resposta informações explicitadas no texto, exige apenas uma busca em sua microestrutura (nível local). Em contraste, as perguntas inferenciais requerem processos cognitivos mais sofi sticados, tornando-as mais difíceis de serem respondidas do que as literais (Buarque, Higino, Miranda, Dubeux, & Pedrosa, 1992;Oakhill, 1984).…”
Section: Prolec-t -Prova De Compreensão De Texto: Análise De Suas Carunclassified